Improving The Ability of Lecturers in The Field of Research at FITK IAIN Syekh Nurjati Cirebon - Aris, Aris; Mahdi, Mahdi; Wijaya, Apriyanda Kusuma (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The policy of coaching the improvement of lecturer performance at the Faculty of Tarbiyah is: a) providing learning opportunities for lecturers at the S2 and S3 levels; b) seminars/workshops/workshops on improving academic abilities, increasing research skills and community service, increasing interest in reading and writing, improving work ethic and campus manners; c) Training/courses on improving the quality of lecturer performance and d) involvement of lecturers in setting institutional quality standards and performance improvement programs. One of the factors causing the low interest of lecturers to conduct research is due to lack of information and understanding of problems related to technical research and c) community service activities are still not optimally carried out, this can be seen from the findings that only a few lecturers carry out community service activities. There are several factors that affect the performance of lecturers, namely: a. Supporting factors ; which includes: 1) support from the leadership of both institutions and faculty leaders as well as cohesiveness and togetherness between lecturers; 2) the existence of policies and objectives of the institution to develop the quality of lecturers; 3) the amount of interest of lecturers to develop and improve the knowledge and skills of lecturers. b. Inhibiting factors include: 1) limited budget financial support that can be provided by IAIN Syekh Nurjati Cirebon institution to finance all further education needs for lecturers; 2) the institution has not been able to provide and provide maximum technical equipment assistance such as laboratories and others; 3) the development of similar universities in various places, and 4) lack of coordination with related institutions, so that good communication and cooperation do not occur.